Experimentação como potencial contribuinte para a formação de conceitos científicos em crianças. - Marcondes, Jamile Silva (Universidade Federal de São Carlos, 2023)
Seeking to find strategies that help in the renewal of Science teaching in Brazil and considering the worrying results obtained by Brazilian students in international exams, we propose an study of Vigotsky's theories and neoVigotskian authors who deal with the construction of scientific concepts by children. This is mainly justified by the scarcity of studies focused on understanding this construction in childhood. Using a qualitative and exploratory methodology, and through bibliographical research, based on the principles present in these theories, we established criteria that guided the analysis of national publications that help in understanding the difficulties associated with conceptual learning in science. The articles published between 2000 and 2020 were found by searching the CAPES Portal and Academic Google. These publications report the use of the experimental approach as a subsidy for the formation of scientific concepts in children attending kindergarten and the early years of elementary school. The Vigotskyian criterion that appears most often is specialized instruction and the ones that appear less frequently are deliberate attention and logical memory. Recognizing the state of intellectual activity of the child on a given object in order to identify the state of attention and memory formation is complex, especially when dealing with a large group.
Experimentation as a potential contributor to the formation of scientific concepts in children.
Keywords: Laboratório de Ciências; Ensino de Ciências; Vigotsky; Science Lab; Science Teaching; Elementary School; Ensino Fundamental; CIENCIAS HUMANAS::EDUCACAO::CURRICULO